Political Power Influences Public Administration System to Achieve Good Governance (Case Study in the General Directorate of Corporate Services, Ministry of State Administration-MAE) - Edio M. P. Soares; Adolmando S. Amaral; Martinus N. Lino; Fernando Dias Gusmão; Leoneto M. Martins (International Journal of Integrative Sciences, 2024)
Good governance is the main objective in the implementation of good government. This research specifically investigates political power to support the achievement of these goals. By using descriptive qualitative method, through in-depth analysis of research objectives such as Understanding causal relationships, identifying key factors, developing a conceptual model, and providing recommendations. This research finds that excessive political intervention in the bureaucracy is a complex problem with deep roots in Timor-Leste's state institutions. The main factors contributing to this problem include an unstable political system, a strong culture of political patronage and institutional weakness significantly influencing the decline of bureaucratic professionalism, conflict of interest, political instability, nepotism and collusion. In addition, this research also identified other factors that play an important role in achieving good governance, such as Recruitment of Civil Servants, Absence of clear roles for Employees, Uncomfortable Working Space, Lack of Facilities for Civil Servants, and Filing Systems. These findings underline the importance of formulating public policies to maintain the neutrality of civil servants, enhance the capacity of civil servants, and build public confidence in their implementation, enforcement of laws and regulations and the proper placement of civil servants. It is hoped that the results of this research can serve as a basis for the government of Timor-Leste to formulate effective and accountable policies.